2018
DOI: 10.1007/s11096-018-0749-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences with multidose drug dispensing: a cross sectional study

Abstract: Background Automated multidose drug dispensing is used to support patients with their medication management. Though multidose drug dispensing systems are frequently used, little is known about patients’ experiences with multidose drug dispensing systems. Objective To explore patients’ experiences with the initiation and use of multidose drug dispensing systems. Setting A survey was carried out with patients using multidose drug dispensing systems through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Our study indicates that the pharmacists only take limited responsibility for patient counselling when supplying MDD prescriptions. Reduced patient counselling about prescription medications upon dispensing might explain why patients using MDD have less knowledge about their medications than patients with ordinary prescriptions [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study indicates that the pharmacists only take limited responsibility for patient counselling when supplying MDD prescriptions. Reduced patient counselling about prescription medications upon dispensing might explain why patients using MDD have less knowledge about their medications than patients with ordinary prescriptions [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDD, which is used by one third of patients receiving home care services in Norway [ 13 , 14 ], is an adherence aid where the patients’ medications are machine-dispensed in disposable plastic bags, usually for 14 days at a time. MDD is believed to increase medication safety by reducing dispensing errors, reducing discrepancies between medication lists, and increasing adherence [ 15 , 16 , 17 , 18 , 19 ]. However, researchers have raised concerns that the MDD system increases the risk of inappropriate prescribing and medication errors, due to the automation of prescribing procedures and insufficient routines for updating the MDD prescriptions [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MDD system is used in the Nordic countries and the Netherlands [ 15 ]. Compared to patients with ordinary prescribing, patients with MDD have fewer serious drug–drug interactions in their medication lists [ 16 , 17 ] and higher medication adherence [ 18 , 19 ] but are also more prone to medication errors in care-level transitions and inappropriate prescribing [ 17 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated the trust towards the technology, which, when implemented, introduces new requirements, both with respect to the patient and with respect to the health professional, who are both required to adjust their daily routines around the ADD robots [17]. Two studies investigated whether ADD robots were initiated for the appropriate patients and reported that one third of the patients were possibly inappropriately initiated on ADD robots, where some patients were experiencing only a few medication problems, and that ADD robots therefore were not needed [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This study was published in 2007 and the ADD technology has progressed since then, and user issues with ADD robots have gradually changed in characteristics. Some of the more recent studies mentioned that not all selected patients were suited for the technology, while others had not lost their capacity to administrate their own medication but, nevertheless, they were initiated on an ADD robot [18,19,22].…”
Section: Patient Perceptions and Experience With Add Robotsmentioning
confidence: 99%